Author Replies to the Comments from Hoffer, Tizzard, and Lewin - Kraus, Katharina (Con-Textos Kantianos. International Journal of Philosophy, 2025)
In what follows, I reply to the comments offered by Noam Hoffer, Jessica Tizzard, and Michael Lewin on my Cambridge Element on Kant’s Ideas of Reason (Cambridge University Press, 2025). Their insightful and diligent comments offer me the opportunity to clarify and refine my interpretation of the regulative use of ideas of reason – a particularly fascinating, but also deeply puzzling aspect of Kant’s theoretical philosophy. I also thank Paula Órdenes for initiating this special issue on my book in Con-Textos Kantianos and for inviting these three distinguished experts to contribute.